Simulation of tandem thin-film silicon solar cells - Jandl, Christine Angelika; Pflaum, Christoph; Dewald, W; et al. (Photonics for Solar Energy Systems III (Proceedings Volume), 2010)
A sophisticated light-management is indispensable for silicon thin-film silicon solar cells based on amorphous (a-Si:H) and microcrystalline (μc-Si:H) silicon. The optical properties of thin-film solar cells have a significant influence on the conversion efficiency. The topology of the nano-textured interfaces affects the optical path and absorption. A rough transparent conductive oxide (TCO) film leads to a high quantum efficiency and shortcircuit current density. Simulations of various geometries indicate the optimal texture. Therefore, we simulate 3-dimensional tandem thin-film solar cells with different interfaces. The roughness can be identified by atomic force microscope (AFM) scans. In order to accurately analyze all aspects of the light propagation in solar cells, numerical simulations of Maxwell's equations are needed. By standard simulation programs for solving Maxwell's equations, it is difficult to simulate realistic textures of the solar cell layers. Therefore, a simulation tool based on the finite difference time domain (FDTD) method and the finite integration technique (FIT) is developed, which is able to integrate AFM scan data. To incorporate the nanostructure of a relevant section in the AFM scans, high computational domains are needed. This leads to a large number of grid points in the resulting discretization. Parallel computations on high performance computers are needed to meet the large computational requirements. The simulations show that the light propagation in the investigated thin-film device is a complex phenomenon depending on the wavelength and phase of the incident light. © 2010 Copyright SPIE - The International Society for Optical Engineering.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.c3sim.simula
Keywords: AFM scan; FDTD simulation; thin-film solar cells